A human laboratory study on the link between alcohol administration and circulating fibroblast growth factor 21 (FGF21) in individuals with alcohol use disorder. (1st April 2023) - Farokhnia, Mehdi; Wang, Tammy; Jourdan, Tony; Godlewski, Grzegorz; Farinelli, Lisa A.; Kunos, George; Leggio, Lorenzo
Abstract: Growing evidence indicates that the crosstalk between the central nervous system and the periphery plays an important role in the pathophysiology of neuropsychiatric conditions, including addictive disorders. Fibroblast growth factor 21 (FGF21) is part of the liver-brain axis and regulates energy homeostasis, metabolism, and macronutrient intake. In addition, FGF21 signaling modulates alcohol intake and preference, and changes in FGF21 levels are observed following alcohol consumption. To further elucidate the relationship between alcohol use and FGF21, we assessed serum FGF21 concentrations in 16 non-treatment seeking individuals with alcohol use disorder (AUD) in a naturalistic outpatient setting, as well as a controlled laboratory experiment that included alcohol cue-reactivity, alcohol priming, and alcohol self-administration in a bar-like setting. FGF21 levels were stable during the outpatient phase when participants received placebo and had no significant lifestyle changes. During the bar-like laboratory experiment, a robust increase in serum FGF21 concentrations was found after the 2-hr alcohol self-administration session (F3, 49 = 23.39, p < 0.001). Percent change in FGF21 levels positively correlated with the amount of alcohol self-administered but did not reach statistical significance. No significant changes in FGF21 levels were found after exposure to alcohol cues or consuming the priming drink. Given the bidirectional link between FGF21 and alcohol, targeting the FGF21 system may be further examined as a potential pharmacotherapy for AUD. Highlights: Growing evidence suggests a close link between FGF21 and alcohol use. Most of the previous data come from preclinical experiments and people without AUD. Alcohol self-administration in a bar-lab increased circulating FGF21 levels in AUD individuals. No changes in FGF21 levels were found after alcohol cue-reactivity or alcohol priming.